Status report of the SINBAD-ARES RF photoinjector and linac commissioning. (November 2019) - Panofski, E; Assmann, R W; Burkart, F; Dorda, U; Floettmann, K; Huening, M; Marchetti, B; Marx, D; Mayet, F; Walker, P A; Yamin, S
Abstract: The accelerator R&D facility SINBAD (Short innovative bunches and accelerators at DESY) will drive multiple independent experiments, including the acceleration of ultrashort electron bunches and the testing of advanced high-gradient acceleration concepts. The SINBAD-ARES (Accelerator Research Experiment at SINBAD) setup hosts a normal conducting RF photoinjector generating a low-charge electron beam, which is afterwards accelerated by an S-band linac section. The linac as well as a magnetic chicane will allow the production of ultrashort bunches with excellent arrival-time stability. The high brightness beam has then the potential to serve as a test beam for next-generation compact acceleration schemes. The setup of the SINBAD-ARES facility will proceed in stages. We report on the current status of the ARES RF gun commissioning and linac setup.